Factors Influencing Intensive Care Unit Nurses' Behavioral Intentions Regarding Providing Artificial Nutrition and Hydration. Issue 5 (October 2015) - Ke, Li-Shan; Lou, Wen-Ching; Hu, Wen-Yu
<x xml:space="preserve">Abstract</x> Providing artificial nutrition and hydration (ANH) to patients with terminal cancer can worsen their symptoms at the end of life. However, withholding or withdrawing ANH raises ethical, emotional, and cultural challenges for health professionals, especially in the intensive care unit (ICU). This study aimed to identify the factors associated with ICU nurses' behavioral intentions toward providing ANH to patients with terminal cancer. A questionnaire survey study was conducted with 616 ICU nurses from 2 medical centers in Taiwan. The results showed that "food and water as basic care, " "requests from patients with terminal cancer for artificial nutrition and hydration, " "ethical acceptability of withholding artificial nutrition and hydration, " physicians, and knowledge of ANH affected nurses' behavioral intentions (adjusted R2 = 0.175). Physician input was most influential on nurses' behavioral intentions toward providing ANH to patients with terminal cancer; thus, nurses should be encouraged to discuss medical decisions with physicians. The study results also suggest that nurses' knowledge of ANH and ethical judgment can be enhanced by scenario-based teaching materials and multidisciplinary team discussions.